2007
DOI: 10.1073/pnas.0705618104
|View full text |Cite
|
Sign up to set email alerts
|

Visual grouping in human parietal cortex

Abstract: To efficiently extract visual information from complex visual scenes to guide behavior and thought, visual input needs to be organized into discrete units that can be selectively attended and processed. One important such selection unit is visual objects. A crucial factor determining object-based selection is the grouping between visual elements. Although human lesion data have pointed to the importance of the parietal cortex in object-based representations, our understanding of these parietal mechanisms in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 36 publications
14
127
3
Order By: Relevance
“…Some recent neurological evidence is consistent with this object file framework: Xu and Chun (2007) distinguished the roles in visual working memory of two brain areas. They found that grouped shapes produced less activation than ungrouped shapes in the inferior intraparietal sulcus (IPS), but not in the superior IPS.…”
Section: Discussionsupporting
confidence: 48%
“…Some recent neurological evidence is consistent with this object file framework: Xu and Chun (2007) distinguished the roles in visual working memory of two brain areas. They found that grouped shapes produced less activation than ungrouped shapes in the inferior intraparietal sulcus (IPS), but not in the superior IPS.…”
Section: Discussionsupporting
confidence: 48%
“…These data support and largely extend the existing evidence (e.g., Jiang et al, 2000;Kemps, 2001;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu & Chun, 2007) showing that Gestalt principles of perceptual organization, like the tendency to perceive and interpret environment in the simple, orderly, and regular way (Law of Pragnanz), and the influence of such attributes of perceptual objects as proximity, similarity, closure, and continuity for their grouping into coherent wholes, which are well-known to organize visual perception, influence also the active maintenance and access of information in VWM during the absence of perceptual stimulation. These results have crucial significance for our understanding of the mechanisms and function of one of the crucial elements of human mind architecture -working memory (i.e., its visual component).…”
Section: Resultssupporting
confidence: 88%
“…Some studies have demonstrated that satisfying such principles by the group of objects not only helps in perceiving them in a particular way, but also facilitates their retrieval from VWM (that is, Gestalt principles "work" even when objects are not accessible perceptually). For instance, objects displayed in proximity to an object that had been cued were more likely reported than distant objects (Woodman, Vecera, & Luck, 2003), and the overall number of reported objects was larger if they were grouped in preceding display than when they were not grouped (Xu & Chun, 2007; for an analogous result pertaining to grouping by similarity see Peterson & Berryhill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this effect could partly reflect low-level Gestalt grouping, which is known to enhance VWM (Anderson et al, 2013;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu, 2006;Xu & Chun, 2007). Although we carefully selected our stimuli to avoid the regular and irregular object pairs differing along low-level dimensions, in Experiment2 we included a control condition to directly rule out any influence of such putative low-level differences.…”
Section: Methodsmentioning
confidence: 99%
“…For example, VWM is enhanced when individual stimuli can be grouped by Gestalt principles or by forming illusory contours (Anderson, Vogel, & Awh, 2013;Peterson & Berryhill, 2013;Woodman, Vecera, & Luck, 2003;Xu, 2006;Xu & Chun, 2007). Similarly, VWM is enhanced when participants learn to associate stimuli through arbitrary spatial contingencies (Brady, Konkle, & Alvarez, 2009;Olson, Jiang, & Moore, 2005).…”
mentioning
confidence: 95%